2000
DOI: 10.2139/ssrn.217428
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Effects of Household Investment in Health in Colombia

Abstract: This study considers the links between primary indicators of health and individual labor productivity in Colombia and explores how additional public expenditures on health may improve individuals' health. Sample statistics show that illness occurs more frequently for women than for men, for less educated than for more educated, for rural than urban residents, and for older individuals. The well educated are considerably taller than those without schooling (6 cm. for males and 4 cm. for females).The empirical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Microeconomic analyses using anthropometric measures (such as the onset of menarche, nutritional status, and stature) and indices of morbidity (such as work days lost due to illness) have consistently shown that health affects worker productivity (Knaul, 1999;Ribero, 1999;Savedoff & Schultz, 2000;Schultz & Tansel, 1997;Strauss & Thomas, 1998).…”
Section: Health Human Capital and Fdimentioning
confidence: 99%
“…Microeconomic analyses using anthropometric measures (such as the onset of menarche, nutritional status, and stature) and indices of morbidity (such as work days lost due to illness) have consistently shown that health affects worker productivity (Knaul, 1999;Ribero, 1999;Savedoff & Schultz, 2000;Schultz & Tansel, 1997;Strauss & Thomas, 1998).…”
Section: Health Human Capital and Fdimentioning
confidence: 99%
“…It has a direct effect on workers' productivity because healthy workers are generally more physically and mentally robust than those afflicted with disease or disability and are less likely to be absent from work because of personal or household illness. Microeconomic analyses using anthropometric measures (such as onset of menarche, stature, and nutritional status) as well as indexes of morbidity, have consistently demonstrated that health affects earnings and productivity (Knaul, 1999;Ribero, 1999;Savedoff and Schultz, 2000;Schultz and Tansel, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn affects productivity later in life (Dasgupta 1993, Strauss and Thomas 1998, and Schultz 1999. The main aim of this study is modelling some of the main determinants of child health in Colombia, where the positive influence of health on wages has also been documented (Ribero, 1999).…”
Section: Introductionmentioning
confidence: 99%